2009
DOI: 10.1111/j.1532-7795.2009.00620.x
|View full text |Cite
|
Sign up to set email alerts
|

A Cross‐Cultural Study of Adolescent Procrastination

Abstract: In this study, we explore academic procrastination and associated motivation variables in 612 adolescents from Canada and Singapore. Few studies have explored adolescent procrastination and no previous studies have investigated adolescent procrastination using a cross-cultural framework. Singaporean adolescents reported higher levels of procrastination and lower levels of self-efficacy for self-regulation than Canadian adolescents. Males across settings reported higher levels of procrastination and lower level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 27 publications
3
45
1
4
Order By: Relevance
“…In addition, academic cheating shows some similarities with academic procrastination as both are more frequently observed in males than in females and in impulsive students who strongly disagree with academic rules (Anderman, Cupp, & Lane, 2009;Brunell, Staats, Barden, & Hupp, 2011;Karim, Zamzuri, & Nor, 2009;Miller, Murdock, Anderman, & Poindexter, 2007). Moreover, students who tend to plagiarise and cheat get lower grades, show a lower level of conscientiousness and self efficacy and attend lessons less frequently than honest students (Yardley, Domènech, Bates, & Nelson, 2009), characteristics which are also described as usual for procrastinators (Ackerman & Gross, 2005;Clariana et al, 2011;Klassen et al, 2009).…”
Section: Academic Cheatingmentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, academic cheating shows some similarities with academic procrastination as both are more frequently observed in males than in females and in impulsive students who strongly disagree with academic rules (Anderman, Cupp, & Lane, 2009;Brunell, Staats, Barden, & Hupp, 2011;Karim, Zamzuri, & Nor, 2009;Miller, Murdock, Anderman, & Poindexter, 2007). Moreover, students who tend to plagiarise and cheat get lower grades, show a lower level of conscientiousness and self efficacy and attend lessons less frequently than honest students (Yardley, Domènech, Bates, & Nelson, 2009), characteristics which are also described as usual for procrastinators (Ackerman & Gross, 2005;Clariana et al, 2011;Klassen et al, 2009).…”
Section: Academic Cheatingmentioning
confidence: 95%
“…From the beginning of its analysis in the 80s, academic procrastination has been significantly and positively related to many educational and personal variables, such as: low conscientiousness as one of the Big Five personality factors, (MacCann, Duckworth, & Roberts, 2009); lack of positive self-image, self-esteem and self-efficacy during the learning process (Klassen et al, 2009); impulsiveness, laziness and lack of discipline when learning (Schouwenbourg & Lay, 1995); lack of motivation to learn and disagreement with academic conditions (Ackerman & Gross, 2005, 2007; and perhaps most importantly, poor academic grades, both in secondary school (e. g. Sub & Prabha, 2003) and university (Clariana, Gotzens, & Badia, 2011, for instance).…”
Section: Academic Procrastinationmentioning
confidence: 99%
“…In academic situations, procrastination is a widespread phenomenon and it has been found that students often procrastinate when approaching academic tasks (e.g. Klassen et al 2009;Lay and Silverman 1996). Several studies have focused on the relationship between academic procrastination and Internet use.…”
mentioning
confidence: 99%
“…The difference between men and women's tendency to procrastinate is another controversial issue among researchers, since although the findings of several studies reported no significant differences between male and females in the incidence of procrastination (; Johnson & Bloom, 1995;Watson, 2001;Ferrari et al, 2007), others reported significant differences (Erdinç, 2009;Klassen et al, 2009). Steel and Ferrari (2013) found a significant correlation between procrastination and gender based on the assumption that men potentially have higher levels of impulsiveness (Strüber, Lück & Roth, 2008, as cited in Steel & Ferrari, 2013) and lower levels of self-control (Higgins & Tewksbury, 2006, as cited in Steel & Ferrari, 2013.…”
Section: Discussionmentioning
confidence: 99%